Influence of Spatial Dispersion on Propagation Properties of Waveguides Based on Hyperbolic Metamaterial - Bartosz Janaszek (MDPI AG, 2021)
In this work, we study the effect of spatial dispersion on propagation properties of planar waveguides with the core layer formed by hyperbolic metamaterial (HMM). In our case, the influence of spatial dispersion was controlled by changing the unit cell’s dimensions. Our analysis revealed a number of new effects arising in the considered waveguides, which cannot be predicted with the help of local approximation, including mode degeneration (existence of additional branch of TE and TM high-β modes), power flow inversion, propagation gap, and plasmonic-like modes characterized with long distance propagation. Additionally, for the first time we reported unusual characteristic points appearing for the high-β TM mode of each order corresponding to a single waveguide width for which power flow tends to zero and mode stopping occurs.